Life stories of caregivers looking after a child with autism in Vietnam - Dung Thi Nguyen (English, 2020)
This study aimed to explore how autistic children form the lives of people who were raising them through life stories shared by caregivers. The research participants included 11 Vietnamese caregivers who were taking care of children diagnosed with autism. A preliminary interview prior to the study was conducted to determine caregivers who would participate in the research and in-depth interviews were carried out with volunteer caregivers. To determine aspects of life stories that shape caregivers’ lives, the study implemented the "Life Story Interview" list. Grounded theory and the constant comparative method, effective research strategies were used to collect and analyze the data. Interviews were conducted in the Vietnamese language. As a result, 6 broad categories of themes were identified related to caregivers’ life stories: (1) psychological consultation, (2) emotions, (3) worries, (4) duties, (5) essential virtues, and (6) hopes. Analyses exposed that although caregivers whose children were autistic underwent a wide range of challenges in their daily lives and had concerns for the future of children, they did a big shot to reorganize their family lives, required themselves highly, and never stopped hoping for a better life.